STUDY OF THE GEOTECHNICAL CHARACTERISTICS OF STRUCTURAL FOUNDATION SOILS: THE CASE OF THE AKPAKPA REGION IN THE REPUBLIC OF BENIN - AGBELELE, Koffi J.; DOKO, KOUANDETÉ VALERY; TIDJANI, Widad; KOUDORO, Julien B. (My University, 2023)
The construction of infrastructure capable of withstanding future hazards in the Akpakpa district requires good control of the foundation soils. The test results showed that the Ayélawadjè and Sodjèatimey soils are class D according to the GTR classification and sub-class D1 (VBS<0. 1): insensitive to water, weakly organic and presenting an over-consolidated state, while the Avotrou soils are of class A according to the GTR classification and of sub-class A4 (IP>40%): very plastic with the following main characteristics: very coherent and almost impermeable. In sum, for the Ayélawadjè and Sodjèatimey soils, it is important to ensure that the soils are uniform and adequately compacted before building on them, as the soils are not very sensitive to water and should not liquefy in the event of heavy rain. However, it is important to ensure that the soils are well drained to avoid problems with moisture and long-term stability. Avotrou soils can be subject to shrinkage and subsidence, which can lead to long-term stability problems.
Keywords: Akpakpa (Cotonou II) - compressible; soils - physical properties - mechanical; properties - geotechnical risks.